Academic Senate Minutes 2003-10-30 - Academic Senate:::::::::
Chair's report deferred to end. Agenda amended and approved. Minutes approved. Appointment of Elaine McHugh and Barbara Lesch-McCaffry to Disability Services Advisory Committee approved. Report from Senate Budget Committee. Reports from President, Provost and Vice President of Administration and Finance. Lecturer's Resolution on Enterprises Surplus postponed until next meeting. Resolution regarding sympathy for our colleagues in Southern California unanimously passed. Reports from Associated Students President, Chair-Elect, APC, EPC and Chair.